2021
DOI: 10.5114/pg.2021.104733
|View full text |Cite
|
Sign up to set email alerts
|

Complications associated with laparoscopic sleeve gastrectomy – a review

Abstract: Laparoscopic sleeve gastrectomy (LSG) is an essential bariatric procedure performed in obese patients, which provides significant weight loss and has a positive impact on obesity-related diseases. However, as with any surgical procedure, it carries the risk of complications. The complications that can arise in patients following LSG are divided into acute (diagnosed within 30 days after the surgery) and late. Early complications that require rapid management include haemorrhage (intraluminal or extraluminal), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Available review and research publications analyzing the subject of postoperative weight loss, BMI, %TWL, %EWL, %EBL after LSG were in line with the results obtained in our study [16,17]. Sleeve gastectomy is considered an effective and safe method of treating obesity [18,19].…”
Section: Beforesupporting
confidence: 90%
“…Available review and research publications analyzing the subject of postoperative weight loss, BMI, %TWL, %EWL, %EBL after LSG were in line with the results obtained in our study [16,17]. Sleeve gastectomy is considered an effective and safe method of treating obesity [18,19].…”
Section: Beforesupporting
confidence: 90%
“…The multicentre study conducted by Benedix et al confirmed that male gender and BMI 50-50.9 kg/m 2 are associated with significantly higher leak rates (2.5 vs. 1.6%, p = 0.02 and p < 0.01) [36]. Patients with gastric leak may be totally asymptomatic or present symptoms of septic shock, such as fever, abdominal pain, tachycardia, tachypnoea and peritonitis [37]. The management of gastric leak is dependent on the clinical status of the patient and it includes: conservative treatment (withholding food and fluids, intravenous hydration, broad spectrum antibiotheraphy, and proton pump inhibitor administration), endoscopic intervention such as implementation of endoprothesis or endoscopic double-pigtail catheter (EDPC) or surgical management (lavage and drainage of peritoneal cavity) [38,39].…”
Section: Discussionmentioning
confidence: 94%
“…GERD is a recognized comorbid condition associated with obesity and is commonly present as a comorbidity at presentation for bariatric surgery. There is a growing body of evidence that LVSG may be associated with worse GERD outcomes, 24,25 likely to because of anatomical, physiological, and physical factors modified through the surgery. 26,27 In the present review, approximately one-third of the study participants who received LVSG and reported GERD as a complication required a conversion to LRYGB to manage this new or worsened comorbidity (17 of 52).…”
Section: Discussionmentioning
confidence: 99%